2004
DOI: 10.1158/0008-5472.can-04-2000
|View full text |Cite
|
Sign up to set email alerts
|

Respective Roles of Serological Status and Blood Specific Antihuman Herpesvirus 8 Antibody Levels in Human Herpesvirus 8 Intrafamilial Transmission in a Highly Endemic Area

Abstract: Transmission of human herpesvirus 8 (HHV-8), the etiological agent of Kaposi's sarcoma, occurs mainly during childhood in endemic countries and, to a large extent, through intrafamilial contacts. To additionally investigate this familial transmission, and especially the role of plasma anti-HHV-8 antibody titers, we conducted a large survey in a village from Cameroon, Central Africa, including 92 families (608 individuals). Plasma samples were tested for specific IgG directed against HHV-8 lytic antigens by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 49 publications
10
43
0
Order By: Relevance
“…9,21 This test which detects antibodies directed principally against lytic HHV-8 antigens is very suitable for use in epidemiologic studies and does not react with any other known HHV-8, including Epstein-Barr virus. It has been used by many groups leading to epidemiological results on HHV-8 that have been widely confirmed by different studies using the same or additional serological tests.…”
Section: Biological Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…9,21 This test which detects antibodies directed principally against lytic HHV-8 antigens is very suitable for use in epidemiologic studies and does not react with any other known HHV-8, including Epstein-Barr virus. It has been used by many groups leading to epidemiological results on HHV-8 that have been widely confirmed by different studies using the same or additional serological tests.…”
Section: Biological Methodsmentioning
confidence: 99%
“…Six studies have provided evidence of correlated HHV-8 serological status between mother and children, one in a Jewish population from Israel 6 and five in the populations of African origin. [7][8][9][10][11] Three of these studies investigating dependences between other biological relatives also found that HHV-8 serological status was strongly correlated between siblings. [8][9][10] This pattern of familial aggregation, which is not accounted for by known risk factors, suggests that host genetic factors may be involved in HHV-8 infection.…”
Section: Human Herpesvirus 8 (Hhv-8) First Identified In 1994 Inmentioning
confidence: 98%
See 2 more Smart Citations
“…In these countries, the seroprevalence of KSHV in different risk groups mirrors the incidence of AIDS-KS, with a seroprevalence rate of between 25% and 50% among homosexual men. On the contrary, the reported seroprevalence of KSHV is high in the adult general population in regions of Brazil, French Guiana, the Mediterranean basin, and Central and Southern Africa, where it ranges from 10% to over 80%; these regions are considered endemic for KSHV (Cunha et al, 2005;Freitas et al, 2002;Kazanji et al, 2005;Klaskala et al, 2005;Mayama et al, 1998;Mbulaiteye et al, 2003;Olsen et al, 1998;Plancoulaine et al, 2000Plancoulaine et al, , 2004Wilkinson et al, 1999). Central African countries, like the Republic of Congo, Uganda, and Zambia, also have the highest KSHV infection rates in the world .…”
Section: B Kshv Epidemiologymentioning
confidence: 99%